Analisis Pengaruh Pengumuman Merger dan Akuisisi Terhadap Abnormal Return Saham dan Kinerja Keuangan Perusahaan (Studi pada perusahaan yang melakukan Merger dan Akuisisi pada Tahun 2011 dan terdaftar di Bursa Efek Indonesia ) - Sihombing, Neddy; Kamal, Mustofa (Faculty of Economics and Business Diponegoro University, 2016)
This Research aimed to see if Merger and Acquisition has an Impact to Financial Performance and Abnormal Return of Companies has listed on Indonesian Stock Exchanged (IDX). Financial Performance is measured by some ratios : Current Ratio (CR), Total Asset Turnover (TATO), Debt to Equity Ratio (DER), Return On Investment (ROI), Earning Per Share (EPS), Abnormal Retun(AR) and Cumulative Abnormal Return (CAR).Population of this research include of companies which conducted Merger and Acquitision activity in the period 2011 and listed on Indonesian Stock Exchange (IDX) and announce merger and acquisition in the period 2011,and data analyzed by non statistic parametric. To answer the hypotesis using Wilcoxon Signed Rank Test and Manova.Analysis of the data used wilcoxon Signed Rank Test and Manova. Empirical Test of Wilcoxon Signed Rank Test show that there are parcial significantion on CR,TATO,DER,ROI and EPS before and after merger and acquisition but for Manova there are no significant for all that ratios. Abnormal Return and Cummulative Abnormal Return show that there are no difference of ratio before and after merger and acquisition.